Pengaruh Penanganan Pascapanen Terhadap Mutu dan Keamanan Pangan Biji Kakao - Munarso, S Joni; Miskiyah, Miskiyah; Thamrin, M (Balai Besar Industri Hasil Perkebunan, 2016)
Production of cocoa beans increasing significantly, but the quality of the seeds low and varied.The main problem is because of the cocoa farmers generally did not apply the recommended techniquefor cultivation and postharvest handling. The aims of this study was to observe the effect of GAP and GMPapplication to the quality and safety of cocoa beans produced by farmer groups. To achieve the aboveobjectives, a study has been conducted in Tinco, District Citta, Soppeng South Sulawesi Province. Thisactivity was done by involving farmer groups with different cultivation technology. The activity included: 1.Study to identify the performance of cocoa cultivation; 2. analysis of the effect of GAP and GMP application toquality and safety of cocoa beans produced by farmer groups. The results showed that the quality of cocoabeans produced by Bunga coklat farmer group better than Mattirodeceng farmer group; the application ofGAP and GMP increased the quality of cacao beans. Model application of GAP and GMP system at Bungacoklat farmer group can be used as a sample of cocoa farm production, quality and sustainability oriented.Keywords : postharvest handling, quality, food safety, cocoa